Are hydropower and irrigation development complements or substitutes?: the example of the Nam Ngum River in the Mekong Basin - Lacombe, Guillaume; Douangsavanh, Somphasith; Baker, J.; Hoanh, Chu Thai; Bartlett, R.; Jeuland, M.; Phongpachith, C. (Informa UK Limited, 2014)
Hydropower and irrigation developments to address rising demand for food and energy are modifying the water balance of the Mekong Basin. Infrastructure investment decisions are also frequently made from a sub-catchment perspective. This paper compares river flows with irrigation development stages in the Nam Ngum sub-basin where the potential for irrigation and hydropower expansion is largely untapped. It shows that full hydropower development in this basin allows irrigation water use to triple, even as it reduces competition with environmental flow requirements. The implications for the wider Mekong are, however, unclear, particularly given uncertainty over parallel transformations elsewhere in the basin.